2011
DOI: 10.1021/nl202447n
|View full text |Cite
|
Sign up to set email alerts
|

Neon Ion Beam Lithography (NIBL)

Abstract: Existing techniques for electron- and ion-beam lithography, routinely employed for nanoscale device fabrication and mask/mold prototyping, do not simultaneously achieve efficient (low fluence) exposure and high resolution. We report lithography using neon ions with fluence <1 ion/nm(2), ∼1000× more efficient than using 30 keV electrons, and resolution down to 7 nm half-pitch. This combination of resolution and exposure efficiency is expected to impact a wide array of fields that are dependent on beam-based lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 31 publications
0
60
0
Order By: Relevance
“…FIB also offers functionalities of imaging, material removal, and deposition ( Figure 6). Neon ions were introduced for a low-fluence, high-resolution lithography, reaching 7 nm half-pitch feature sizes with 1 ion/nm 2 dose, at which a ~10 3 times more efficient fabrication was achieved compared with standard Ga-ion 30 keV exposure [84].…”
Section: Focused Ion Beamsmentioning
confidence: 99%
“…FIB also offers functionalities of imaging, material removal, and deposition ( Figure 6). Neon ions were introduced for a low-fluence, high-resolution lithography, reaching 7 nm half-pitch feature sizes with 1 ion/nm 2 dose, at which a ~10 3 times more efficient fabrication was achieved compared with standard Ga-ion 30 keV exposure [84].…”
Section: Focused Ion Beamsmentioning
confidence: 99%
“…Winston et al have shown that NIBL is capable of patterning lines with a 7 nm line width. 68 Figure 10(a) displays a developed grating created from NIBL. Most notably, the dose required to create the line structures in the HSQ were $10Â lower than that of He þ ions and $1000Â lower than electrons.…”
Section: Helium and Neon Ion Beam Lithographymentioning
confidence: 99%
“…Both LSF and PSF exhibit powerlaw-like dependences (i.e. high contrast) 10 due to high sensitivity of CAR to He-ions and spatial resolution. 6 Furthermore, it is worth mentioning that it has been reported that optical critical dimension (OCD) scatterometry provides a more accurate measure of CD, for a valid number of similar features, than CD-SEM metrology.…”
Section: Point-spread Function For Shibl In Carmentioning
confidence: 99%